2021
DOI: 10.3390/pathogens10030255
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Giardia duodenalis, Cryptosporidium spp., and Blastocystis sp. in Symptomatic and Asymptomatic Schoolchildren in Zambézia Province (Mozambique)

Abstract: Infections by the protist enteroparasites Giardia duodenalis, Cryptosporidium spp., and, to a much lesser extent, Blastocystis sp. are common causes of childhood diarrhoea in low-income countries. This molecular epidemiological study assesses the frequency and molecular diversity of these pathogens in faecal samples from asymptomatic schoolchildren (n = 807) and symptomatic children seeking medical attention (n = 286) in Zambézia province, Mozambique. Detection and molecular characterisation of pathogens was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Remarkably, sequence data revealed that all ST1 isolates detected involved allele 8 and, to a much lesser extent, alleles 1 and 7. In contrast, human infections/colonisation by ST1 are primarily due to allele 4 in both developed or developing countries [ 72 , 73 ]. Taken together, this data suggests that different host-adapted genetic variants of ST1 are circulating in human and NHP populations.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, sequence data revealed that all ST1 isolates detected involved allele 8 and, to a much lesser extent, alleles 1 and 7. In contrast, human infections/colonisation by ST1 are primarily due to allele 4 in both developed or developing countries [ 72 , 73 ]. Taken together, this data suggests that different host-adapted genetic variants of ST1 are circulating in human and NHP populations.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium viatorum was originally reported in the UK in travellers returning from India and formally described as a human species in 2012 [ 73 ]. Since then, C. viatorum have been described in humans from Australia [ 66 ], China [ 114 ], Columbia [ 68 ], Ethiopia [ 34 , 64 , 74 ], India [ 63 , 67 ], Mozambique [ 62 ], Myanmar [ 65 ], Nigeria [ 69 , 70 ] and Swedish patients (who had returned from Kenya or Guatemala) [ 51 , 71 , 72 ]. It has also been detected in urban wastewater in China [ 204 ].…”
Section: Zoonotic Cryptosporidium Species and Genotypesmentioning
confidence: 99%
“…Certainly, this is a hospital-based cross-sectional study, thus, biases toward sick and symptomatic children. However, a cross-sectional study in Zambezia province, Mozambique, during 2017–2019 observed similar Giardia infection PCR detected prevalences in health centers and in schools in children between 3 and 14 years old (42% and 41.7%, respectively) [ 21 ]. Moreover, other studies in other Mozambican regions also showed Giardia infection among the most prevalent intestinal parasites.…”
Section: Discussionmentioning
confidence: 99%
“…and E. histolytica , were less prevalent in children attending healthcare in Manhiça district. Regarding Cryptosporidium spp , other hospital-based studies in Mozambique also detected prevalence below 6% by microscopy or PCR [ 21 , 24 ]. Nonetheless, Cryptosporidium spp .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation